ALBUMIN-BASED NANOPARTICLES FOR DRUG COMBINATION IN INFLAMMATORY BOWEL DISEASE. (21st January 2021) - Zhang, Sufeng; Cho, Won Joon; Jin, Amy; Korzenik, Josh; Lennerz, Jochen; Traverso, Carlo
Abstract: Despite recent therapeutic advances in the treatment of inflammatory bowel disease (IBD), the off-target systemic side effects of small-molecule drugs or biologics remain problematic. Targeting the site of intestinal inflammation offers an approach to maximize potential therapeutic benefits while minimizing systemic side effects. Importantly, drug combination provides the possibility of tackling IBD through different pathways that could improve the treatment outcome. Here we introduced an inflammation-targeting drug delivery system utilizing albumin-based nanoparticles (NPs) for drug combination with relevance for IBD treatment. The pathophysiological features of the inflamed mucosa in IBD include the disrupted mucosal barrier and increased intestinal permeability; inflammation of the colonic mucosa is also accompanied by an in-situ secretion and accumulation of positively charged proteins at the site of inflammation 1, 2 . We formulated the NPs using human serum albumin (HSA) with heparin coating (termed as HEP-HSA NPs) to increase the negative surface charge to interact with the accumulated positively charged proteins at the inflamed mucosa. Both small-molecule drugs and biologics were chosen to be encapsulated in these NPs, including budesonide (BUD), vancomycin (Vanco), and granulocyte macrophage colony-stimulating factor (GM-CSF). As an example of drug combination, we loaded BUD and GM-CSF simultaneously in the HEP-HSA NPs. The dual-drug loaded HEP-HSA NPs exhibited a higher anti-inflammatory effect than both of the single-drug loaded NPs in vitro and selectively bound to the inflamed intestine after enema administration in vivo in a murine model of colitis. Importantly, analyses of the physicochemical characteristics and targeting capacities of these NPs indicate that HEP coating modulates NP binding to the inflamed intestine, providing a foundation for future development of inflammation-targeting NP formulations 3 . Furthermore, by analyzing disease parameters in individual mice, we also investigated the correlation between NP targeting and disease activity in the inflamed colon, which provides an approach to further our understanding on the underlying interactions between NPs and the biological interface in colitis. References: 1. Tirosh B, Khatib N, Barenholz Y, et al. Transferrin as a luminal target for negatively charged liposomes in the inflamed colonic mucosa. Mol Pharm 2009;6:1083–91. 2. Zhang S, Ermann J, Succi MD, et al. An inflammation-targeting hydrogel for local drug delivery in inflammatory bowel disease. Sci Transl Med 2015;7:300ra128. 3. Zhang S, Cho WJ, Jin AT, et al. Heparin-Coated Albumin Nanoparticles for Drug Combination in Targeting Inflamed Intestine. Adv Healthc Mater 2020;9:e2000536.